Lessons from NAFTA for Latin America and the Caribbean - Lederman, Daniel (Palo Alto, CA: Stanford University Press, 2013)
Analyzing the experience of Mexico under the North American Free Trade Agreement (NAFTA), "Lessons from NAFTA" aims to provide guidance to Latin American and Caribbean countries considering free trade agreements with the United States. The authors conclude that the treaty raised external trade and foreign investment inflows and had a modest effect on Mexico's average income per person. It is likely that the treaty also helped achieve a modest reduction in poverty and an improvement in job quality.